2022
DOI: 10.3390/ijerph19127067
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Optimism and Pessimism on Adolescents’ Subjective Well-Being: Mediating Roles of Reappraisal and Acceptance

Abstract: Prior research has found the differential strength of optimism and pessimism in predicting physical health. However, whether similar findings would be obtained in predicting subjective well-being and the possible underlying mechanisms are still unclear. This study examined the relative strength of optimism and pessimism in predicting adolescent life satisfaction and depression, and further explored the possible mediating mechanisms from the perspective of emotion regulation. A sample of 2672 adolescents (Mage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(166 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, Zeng et al ( 18 ) suggested that optimism is a central feature of adolescent well-being, and similar results were reported in subsequent studies. For example, Zou et al ( 19 ) suggested that optimism seems to be a significant predictor of life satisfaction among adolescents.…”
Section: Adolescents' Well-being: the Epoch Modelmentioning
confidence: 99%
“…Furthermore, Zeng et al ( 18 ) suggested that optimism is a central feature of adolescent well-being, and similar results were reported in subsequent studies. For example, Zou et al ( 19 ) suggested that optimism seems to be a significant predictor of life satisfaction among adolescents.…”
Section: Adolescents' Well-being: the Epoch Modelmentioning
confidence: 99%
“…Studies have shown that acceptance strategies are effective in lessening frustrating mood and depressive symptoms (Shiri et al, 2022;Zou et al, 2022). In addition, mounting randomized controlled trials or quasi-experimental studies have also confirmed that acceptance and commitment therapy (ACT) and mindfulness-based cognitive therapy (MBCT) are promising solutions to improving negative experience in adolescents, such as depression and anxiety (Pinhas-Hamiel and Hamiel, 2020;Musa et al, 2021;Shiri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to cognitive reappraisal, acceptance strategies do not require reframing emotional stimuli by subjective reassessment and recognition; alternatively, acceptance strategies emphasize the proactive acceptance of the negative emotion arousal and to let it be. Studies have shown that acceptance strategies are effective in lessening frustrating mood and depressive symptoms (Shiri et al, 2022 ; Zou et al, 2022 ). In addition, mounting randomized controlled trials or quasi-experimental studies have also confirmed that acceptance and commitment therapy (ACT) and mindfulness-based cognitive therapy (MBCT) are promising solutions to improving negative experience in adolescents, such as depression and anxiety (Pinhas-Hamiel and Hamiel, 2020 ; Musa et al, 2021 ; Shiri et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As regards the parents themselves, parental burnout can not only give rise to suicidal and escape ideations [5], but also may lead to external problems such as substance and behavioral addictions and sleep disorders [6]. Prolonged exposure to this negative state results in a significant decrease in the individual's life satisfaction and subjective well-being, and is highly likely to lead to depressive symptoms [7][8][9][10]. At the biological level, parental burnout leads to a dysregulation in the hypothalamic-pituitary-adrenal (HPA) axis [11], which is most likely causally implicated in the somatic complaints and sleep difficulties experienced by burntout parents and may also be possibly associated with the rise in child-directed aggression [12].…”
Section: Introductionmentioning
confidence: 99%